Early leaving from vocational education and training : Germany - Hensen-Reifgens, Kristina Alice [Verfasser] (My University, 2014)
One of the headline targets within the Europe 2020 strategy is reducing the share of early leavers from vocational education and training to less than 10 per cent. This article aims to help understanding dropping out from VET in Germany. For this purpose, it deals with the following topics: reasons why learners drop out from VET; measures within VET programmes to prevent learners from 'dropping out'; measures to encourage learners to re-engage in VET/education and training once they have dropped out from VET. The article is the first one of a set of articles prepared within Cedefop's ReferNet network. It is based on a common template prepared by Cedefop for all ReferNet partners. (BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); Berufsbildungspolitik; Ausbildungsabbruch